Long-term NIR variability in the UKIDSS Ultra Deep Survey: a new probe of AGN activity at high redshift. Issue 2 (11th February 2020) - Elmer, E; Almaini, O; Merrifield, M; Hartley, W G; Maltby, D T; Lawrence, A; Botti, I; Hirst, P
ABSTRACT: We present the first attempt to select active galactic nuclei (AGN) using long-term near-infrared (NIR) variability. By analysing the K -band light curves of all the galaxies in the UKIRT Infrared Deep Sky Survey (UKIDSS) Ultra Deep Survey, the deepest NIR survey over ∼1 deg 2, we have isolated 393 variable AGN candidates. A comparison to other selection techniques shows that only half of the variable sources are also selected using either deep Chandra X-ray imaging or Infrared Array Camera (IRAC) colour selection, suggesting that using NIR variability can locate AGN that are missed by more standard selection techniques. In particular, we find that long-term NIR variability identifies AGN at low luminosities and in host galaxies with low stellar masses, many of which appear relatively X-ray quiet.